Social Media as a Source of Medical Information for Parents of Premature Infants: A Content Analysis of Prematurity-Related Facebook Groups - Taylor, Katherine; Havinga, Jaclyn; Moore, Brittney; Tumin, Dmitry; Bear, Kelly (American Journal of Perinatology, 2021)
Objective Parents are increasingly turning to social media for medical recommendations. Our objective was to systematically examine posts on Facebook for parents of infants hospitalized in the neonatal intensive care unit (NICU) to analyze how advice on medical topics was requested and given, and whether this advice was potentially medically inappropriate.Study Design One hundred Facebook groups were screened for study eligibility. In each group, up to 400 posts on medical topics were evaluated. The first 10 comments of each post were classified based on content and presence of medical advice. Appropriateness of advice was evaluated by a neonatologist.Results Of 28 groups meeting study criteria, 10 permitted access for data collection. We identified 729 posts requesting medical advice of which 29% referenced the NICU period. Posts on diagnosis and development (30 and 32% of posts, respectively) were the most common topics, and most likely to receive advice (78 and 76% of posts on these topics, respectively). We identified 238 comments containing potentially inappropriate medical advice and 30 comments recommending going against medical advice.Conclusion Parents are utilizing Facebook as a source of support and medical information. Parents are most likely to give development-related advice from their own parenting experiences. The high percentage of posts requesting advice about diagnosis and development in the post-NICU stage suggests parents seek increased anticipatory guidance.Key Points
Keywords: social media; Facebook; NICU; neonatal; medical advice; medical information; prematurity